La Personalidad como predictora de dificultades cotidianas en la adolescencia - Molina Martín, Susana; Inda Caro, Mercedes; Fernández García, Carmen María (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN Los objetivos de este trabajo han sido: estudiar la adecuación de los datos al modelo de cinco factores e identificar rasgos de personalidad en adolescentes que manifiestan tener diversas problemáticas. Para ello se utilizaron dos instrumentos de evaluación, el Cuestionario de Personalidad para Adolescentes (16PF-APQ) y el Cuestionario Autoaplicado de Síntomas (CAS), que se administraron a ciento ocho estudiantes de último curso de educación obligatoria. Los resultados señalan que la muestra se adecua al modelo de cinco factores y que hay rasgos de personalidad que parecen explicar mejor o predecir la presencia de ciertas problemáticas en la adolescencia. ABSTRACT The aim of this research is twofold. Firstly, it studies the adjustment of the data with the five-factor model. Secondly, it intends to describe and identify personality traits in adolescents who have manifested different problems in their daily life. For this purpose, two evaluation instruments were used: the Adolescent Personality Questionnaire (16PF-APQ) and the Adolescents Self-report of Symptoms (C.A.S.). This last one is based on Rogers, Bagby and Dickens’ instrument, Structured Interview Re- ported Symptoms (1990, 1991, 1992). These tests were administered to a sample of a hundred and eight students who were in their last year of compulsory secondary education. The results of the study suggest that the sample fits with the five factor model and that there are some personality traits that seem to explain the existence of life’s difficulties (questions concerning matters of anger or aggression, discouragement, worry, poor body image, alcohol or drugs, overall trouble, familiar context, scholar context and strategies coping). All the already mentioned results allow us to formulate certain indications or suggestions which would need to be taken into account in future research.